Morphology of pollen grains of the Polygalaceae family from the Valley of Mexico - Arreguín-Sánchez, Ma. de la Luz; Palacios-Chávez, Rodolfo; Quiróz-García, David Leonor; Ramos-Zamora, Delfina (Instituto de Ecología, A.C., 1988)
The pollen morphology of the Polygalaceae of the Valley of Mexico is studied using LM and SEM, for all seven species: Monnina ciliolata DC., Polygala alba Nutt., P. appressipilis Blake, P. compacta Rose, P. myrtilloides Wild., P. mexicana Moc., and P. subalata S. Wats. Pollen grains belonging to the family do not present great differences in ornamentation, from or size at the generic or specific levels: nevertheless, the taxa studied can be divided into two groups based on furrow number. Polygala alba, P. mexicana and P. subulata all have 8 to 10, while Monnina ciliolata, P. appressipilis, P. compacta and P. mytilloides have 14 to 20. Comparing the taxonomic studies in Polygala with the present pollen study, it is observed that the species with 8 to 10 furrows correspond to subgenus Orthopolygala (subg. Polygala) and the species with 14 to 20 furrows to subgenus Hebecarpa (Blake, 1916).